Rural Media Literacy: Youth Documentary Videomaking as a Rural Literacy Practice - Damiana Gibbons Pyles (Journal of Research in Rural Education, 2016)
Through an analysis of a corpus of youth-produced documentary video data collected at a youth media arts organization in rural Appalachia, I explore how these rural youth engaged in media literacy practices through creating documentary videos about themselves and their community. Using a theoretical foundation in literacies research, especially rural literacies, I conducted a modal analysis of a set of documentaries produced by rural youth through which I develop a working defi nition of rural media literacy, a literacy practice that respects the knowledge, identities, and values of local, rural areas and people expressed through rural youths' media literacy productions.